Molecular evolutionary trends and feeding ecology diversification in the Hemiptera, anchored by the milkweed bug genome - Traverso, Lucila María (2017)
Background: The Hemiptera (aphids, cicadas, and true bugs) are a key insect order whose members offer a close outgroup to the Holometabola, with high diversity within the order for feeding ecology and excellent experimental tractability for molecular genetics. Sequenced genomes have recently become available for hemipteran pest species such as phloem-feeding aphids and blood-feeding bed bugs. To complement and build upon these resources, we present the genome sequence and comparative analyses centered on the large milkweed bug, Oncopeltus fasciatus, a seed feeder of the family Lygaeidae. Results: The 926-Mb genome of Oncopeltus is relatively well represented by the current assembly and official gene set, which supports Oncopeltus as a fairly conservative hemipteran species for anchoring molecular comparisons. We use our genomic and RNA-seq data not only to characterize features of the protein-coding gene repertoire and perform isoform-specific RNAi, but also to elucidate patterns of molecular evolution and physiology. We find ongoing, lineage-specific expansion and diversification of repressive C2H2 zinc finger proteins and of intron gain and turnover in the Hemiptera. These analyses also weigh the relative importance of lineage and genome size as predictors of gene structure evolution in insects. Furthermore, we identify enzymatic gains and losses that correlate with hemipteran feeding biology, particularly for reductions in chemoreceptor family size and loss of metabolic reactions within species with derived, fluid-nutrition feeding modes. Conclusions: With the milkweed bug genome, for the first time we have a critical mass of sequenced species representing a hemimetabolous insect order, substantially improving the diversity of insect genomics beyond holometabolans such as flies and ants. We use this addition to define commonalities among the Hemiptera and then delve into how hemipteran species' genomes reflect their feeding ecology types. Our novel and detailed analyses integrate global and rigorous manual approaches, generating hypotheses and identifying specific sets of genes for future investigation. Given Oncopeltus's strength as an experimental research model, we take particular care to evaluate the sequence resources presented here, augmenting its foundation for molecular research and highlighting potentially general considerations exemplified in the assembly and annotation of this medium-sized genome.